Cursos de licenciatura na área de ciências: a temática inclusão escolar de alunos com necessidades educacionais especiais - Basso, Sabrina Pereira Soares [UNESP] (2015)
An important transformation of school reality was the perspective of inclusive education, officially adopted in Brazil, in the late twentieth century, creating new demands on teacher education, including science teaching area. Faced with the incipient research on inclusive Education / Special Education and initial training of teachers for teaching of science, this study sought to answer the following question> how is the initial teacher training in the area of Sciences (Biology, Physics and Chemistry) for Inclusive Education, in particular for the inclusion of students with disabilities? The general objective of this study was to analyze the initial training of teachers in the area of Sciences (Biology, Physics and Chemistry) for inclusive Education / Special Education in undergraduate courses in state public universities in the state of São Paulo. To facilitate the achievement of the proposed objective was developed from a study following the qualitative and quantitative research methodology. The degree courses courses were analyzed in Biology, Physics and Chemistry, UNESP, UNICAMP and USP. For the analysis of the political pedagogical project and teaching plans, we opted for the documentary analysis. Semi-structured with the coordinators of the courses were interviewed. The questionnaire was administered to students in the final year of a bachelor degree in Sciences, faculty members who teach courses that address the theme of Inclusive Education and the teachers responsible for the discipline of Supervised Internship. For the analysis of interviews and questionnaires the content analysis of Laurence Bardin was used. It was found the inclusion theme of Inclusive Education in only three Pedagogical Policy Projects and its little insertion in disciplines of the pedagogical area. Most undergraduates understand Inclusive Education as education for pupils with special edeucational needs; they aim at more difficult to inclusive shool the...